Female Representation in Pakistani Digital Media: A Comparative Critical Feministic Study of Rehman’s “Mere Pas Tum Ho" & Ahmed’s “Sinf-e-Ahan” - Noor, Ayesha; Hanif, Mona; Safdar, Anum (Pakistan Journal of Humanities and Social Sciences, 2024)
The present study aims to explore the portrayal of female characters by male and female writers in Pakistani digital media. Hence, the primary objective of this study is to figure out which gender is focused to show the strong and positive side of women. Meanwhile, the secondary objective is to trace the gender stereotypes in the context of the two particular dramas. Fairclough (1992) model of critical discourse analysis has been applied along with Beauvoir (1997) notion of feminism as the framework of the study. Two Pakistani dramas namely “Mere Pas Tum Ho" and Sinf-e-Ahan" have been the source of data. Meanwhile, a particular sample of twenty scenes from ten episodes of each drama has been selected through purposive sampling. However, the findings revealed that in Pakistani Digital media, male writers intend to portray women as negative, disloyal, passive, and emotionally frail creatures while on the other hand, female writers are trying to show the positive side of women by presenting them as strong and independent ones who are challenging patriarchal norms by pursuing their careers and fighting against every unjust thing they see happening around.